Customers' Adoption and use of E-banking services: A Study in Public Commercial Banks, Sri Lanka (Global Journal of Management and Business Research, 2018)
Internet banking plays a major role in banking sector. It seems that commercial banks has not yet attracted sufficient customers to use internet banking when compared with the other developed and developing countries in Sri Lanka. In many developed countries growth has been experienced in banking sector due to evolution of internet banking in last two decades. Huge investments have been made by different banks in interactive information systems in order to provide advanced services to their customers and in return expect increased profits and market share. However, if customers fail to accept or fully utilize such services than the chances of losses from these investments are likely. In this study the researcher concerns the factors influencing on the customer adoption and uses of e- banking system in Sri Lankan public commercial banks’ perspective especially in Colombo District. The research framework based on the factors which mainly include customer attitude, subjective norms, perceived behavioral Control, A Questionnaire survey was conducted to gather the data and 231 complete responses were gathered from banking customers who were internet users from Colombo district. Public commercial banks have been selected in Colombo District based on non-probability sampling method (quota sampling method). Multiple regression has been used for the analysis. Researcher found the factors influencing on the customer adoption of e- banking and gives recommendations in this study to identify the factors influencing on customer adoption of internet banking in the study area.
Keywords: e-banking; customer attitude; subjective norms; perceived behavioral control; srilanka; commercial banks